Bacterial symbiont sharing in Megalomyrmex social parasites and their fungus‐growing ant hosts. Issue 12 (9th June 2015) - Liberti, Joanito; Sapountzis, Panagiotis; Hansen, Lars H.; Sørensen, Søren J.; Adams, Rachelle M. M.; Boomsma, Jacobus J.
Abstract Bacterial symbionts are important fitness determinants of insects. Some hosts have independently acquired taxonomically related microbes to meet similar challenges, but whether distantly related hosts that live in tight symbiosis can maintain similar microbial communities has not been investigated. Varying degrees of nest sharing between Megalomyrmex social parasites (Solenopsidini) and their fungus‐growing ant hosts (Attini) from the genera Cyphomyrmex, Trachymyrmex and Sericomyrmex allowed us to address this question, as both ant lineages rely on the same fungal diet, interact in varying intensities and are distantly related. We used tag‐encoded FLX 454 pyrosequencing and diagnostic PCR to map bacterial symbiont diversity across the Megalomyrmex phylogenetic tree, which also contains free‐living generalist predators. We show that social parasites and hosts share a subset of bacterial symbionts, primarily consisting of Entomoplasmatales, Bartonellaceae, Acinetobacter, Wolbachia and Pseudonocardia and that Entomoplasmatales and Bartonellaceae can co‐infect specifically associated combinations of hosts and social parasites with identical 16S rRNA genotypes. We reconstructed in more detail the population‐level infection dynamics for Entomoplasmatales and Bartonellaceae in Megalomyrmex symmetochus guest ants and their Sericomyrmex amabilis hosts. We further assessed the stability of the bacterial communities through a diet manipulation experiment and evaluated possible transmission modes in shared nests such as consumption of the same fungus garden food, eating of host brood by social parasites, trophallaxis and grooming interactions between the ants, or parallel acquisition from the same nest environment. Our results imply that cohabiting ant social parasites and hosts may obtain functional benefits from bacterial symbiont transfer even when they are not closely related.